IMPLEMENTASI METODE CERITA ISLAMI DALAM PENANAMAN NILAI-NILAI PENDIDIKAN AGAMA ISLAM DI TK - Anjarsari Anjarsari; Eki Agustin (Institut Madani Nusantara, 2022)
The storytelling method aims to equip kindergarten children with learning experiences through oral storytelling. The world of children is a beautiful world. Much of its beauty is helped by the stories someone tells us. Our imagination grows well with it. The growth of imagination is very important to shape the innovative thinking of the future. Departing from the problems formulated above, this study applies the Islamic narrative method in developing the values ??of Islamic religious education, the Islamic narrative method in absorbing the values ??of Islamic religious education. explain support and oppression. Factors of Islamic Storytelling Method in Educational Values ??to Explain Islamic Religious Education in Raudlatul Athfal Mustika Bangsa Kutajaya Cicrug. In accordance with the title of the research project, Application of Islamic Narrative Law to convey the value of Islamic religious education, this research uses a descriptive research approach. Descriptive research is research that aims to collect information about the state of existing symptoms, namely the state of symptoms at the time the research was conducted. The results showed that the application of Islamic narrative law in absorbing the values ??of Islamic religious education at RA Mustika Bangsa Kutajaya Cicrug was very effective and useful in teaching teachings about morals and beliefs.